CORONARY REPERFUSION IN SENILE PATIENTS WITH ACUTE ST ELEVATION MYOCARDIAL INFARCTION - E. V. Vyshlov (Российский кардиологический журнал, 2016)
The review is focused on the main data about course specifics of myocardial infarction with ST elevation (STEMI) in senile patients that influences rate of performing urgent coronary reperfusion. Analysis of literature data has been done, on the topics of efficacy and safety of the main methods of coronary reperfusion — thrombolysis, primary percutaneous intervention (PCI) and their combinations under the pharmacoinvasive reperfusion — in patients ≥75 y.o. As a result of such analysis it is accused that the Open artery theory (Braunwald E.), according which the main task for STEMI patients is acute coronary reperfusion, is truthful not only for general population, but for ≥75 as well. Advantage of primary PCI over thrombolysis in senile patients is shown in randomized trials, but is not proved by registries data. High rate of comorbidity restricts the abilities for reperfusion actions in randomized trials as in real practice. Hence it is important to study further the indications and contraindications for urgent reperfusion in such cohort. Especially it is important for early routine PCI in stable senile patients after thrombolysis, with secondary signs of coronary reperfusion.